Development of Non-Medical Rehabilitation Program to Overcome Weaknesses in Hemodialized Patients in Medan City Hospital - Silaen, Harsudianto; Roby Purba, Jhon; Taufik Daniel Hasibuan, Muhammad (Rifa'Institute, 2022)
Introduction: The problems that occur show that 71.0% to 92.2% of patients experience weakness and that weakness is the most important condition to be observed in patients with chronic kidney failure and it is necessary to have a program to prevent weakness before and after hemodialysis. Objective: The aim of research in research is to develop a non-medical rehabilitation program to overcome weaknesses in hemodialysis patients at Medan City Hospital and facilitate health facilities in the establishment of New Service Programs. Method: The data analysis method used is Action Research. Quantitative data analysis by testing the validity of the instrument was carried out using the Content Validity Index (CVI) with a value of 0.88, while qualitative data analysis used content analysis, namely colaizzi. Result and Discussion: The results of this study were obtained, namely standard operating procedures for the Non-Medical Rehabilitation Program to Overcome Weaknesses in Hemodialysis Patients at Medan City Hospital. After the non-medical rehabilitation program was carried out according to the stages of this study, the 16 hemodialysis patient participants said that the weakness had decreased. Conclusion: Knowledge of human resources (nurses and therapists/physiotherapy) increases 100% with recommendations for standard operating procedures to be carried out in hospitals. This research is intended to be carried out in several hospitals that have hemodialysis and medical rehabilitation services at the level of applied research